Morphometric Analysis, Genetic Diversity, and Population Structure of Two Spiny Lobster Species from Palu Bay, Central Sulawesi, Indonesia - Serdiati, Novalina; Nurdin, Muh Saleh; Hasanah, Nur; Putra, Aswad Eka; Mansyur, Kasim; Azmi, Fauziah; Haser, Teuku Fadlon; Islamy, Raden Adharyan (UI Scholars Hub, 2025)
Indonesia could potentially benefit significantly from economically important lobster species of the Panulirus genus, particularly the painted spiny lobster (P. versicolor) and the white-whiskered coral crayfish (P. femoristriga). Effective conservation decisions relating to these species require detailed knowledge of morphological variation and genetic relationships, especially in Palu Bay, Central Sulawesi, which is broadly considered pivotal for lobster conservation management. In this study, we conducted morphometric and genetic analyses to examine diversity and population structure of P. versicolor and P. femoristriga. From May to November 2021, a total of 72 specimens were collected in Kabonga Village, Donggala Regency, consisting of 53 P. versicolor and 19 P. femoristriga. Using the truss morphometric method, we divided the lobster body into four regions and measured 24 morphometric characters. Despite shared external traits, our truss morphometric analysis indicated that the two species represent distinct populations. Genetic analyses were performed on representative samples (n = 2) using mitochondrial COI sequences, confirming their identity as P. versicolor and P. femoristriga. Although haplotype analysis revealed genetic variability, the analysis of molecular variance (AMOVA) showed that the two populations shared genetic traits and had no significant genetic differences. Haplotype networks further indicated interconnections with more than one nucleotide substitution among haplotypes. Our findings demonstrate that although P. versicolor and P. femoristriga coexist in Palu Bay, they are morphologically distinct and require separate management and conservation strategies. These results provide baseline information for developing sustainable lobster fishery management in Central Sulawesi.